Community Leader Participation in the Extension Programme Decision-Making Process - Ahmad, Aminah; Forest, Laverne B. (1989)
This research studied participation levels of community leaders in the extension programme decision-making process, as perceived by extension staff. The objectives were to determine (1) if the perceived particpation levels differed by tasks associated with two different types of programme decisions, (2) if the perceived participation levels varied by tasks associated with different steps of the decision-making process, and (3) how the perceived participation levels relate to extension staffs attitudes toward community leader participation, for each type of programme decision. This research found the following: (1) Contrary to expectation, the perceived participation levels of community leaders did not differ for both 'more technical' and 'less technical' programme decisions: (2) The perceived participation levels varied by the different decision-making steps,. Community leaders were perceived to participate least at the choice of alternatives and the plan of action steps of decision making. (3) Only for 'less technical' programme decisions were attitudes of extension staff positively related to perceived community leader participation levels.